Pakistan: a historical and contemporary look - Bajwa, Farooq Naseem (Oxford University Press Karachi, 2003)
Pakistan: A Historical and Contemporary Look offers an in-depth analysis of Pakistan's past and present, exploring its history, politics, and societal challenges.